Pengaruh Ice Breaking Terhadap Keaktifan Belajar Siswa Pendidikan Agama Kristen (PAK) Kelas VIII SMP Negeri 1 Sipoholon Kabupaten Tapanuli Utara Tahun Pembelajaran 2023/2024 - Meta Rosianna; Masniar Hernawaty Sitorus; Rida Gultom; Goklas J. Manalu; Raikhapoor Raikhapoor (Jurnal Pendidikan Agama dan Teologi, 2024)
This research aims to determine the magnitude of the influence of Ice Breaking on the Learning Activeness of Christian Religious Education (PAK) of Class VIII Students of SMP Negeri 1 Sipoholon for the 2023/2024 Academic Year." The hypothesis of this research is that there is a positive and significant influence of Ice Breaking on the learning activeness of class VIII PAK students at SMP Negeri 1 Sipoholon, North Tapanuli district for the 2023/2024 academic year. This research is correlational research that uses inferential quantitative methods. The population is all class VIII students at SMP Negeri 1 Sipoholon who are Protestant Christians, totaling 190 people. Sample Based on Random Sampling of Class VIII Students of Sipoholon State Middle School, 15% of 190 students were taken, namely 30 people. The instrument for this research is a closed questionnaire with 34 items. The questionnaire trial was carried out on 29 students outside the research respondents. "The results of the analysis of the values rcount=0.745>rtabel=0.361 and tcount=5.909>2.048 show that there is an influence between Ice Breaking on the Learning Activeness of Christian Religious Education (PAK) of Class VIII Students of SMP Negeri 1 Sipoholon in the 2023/2024 Academic Year." Hypothesis testing obtained Fcount=5.994>Ftable=2.16. This research concludes that there is a positive and significant influence between Ice Breaking on the Learning Activeness of Christian Religious Education (PAK) of Class VIII Students of SMP Negeri 1 Sipoholon for the 2023/2024 Academic Year" amounting to 55.5%, so H0 is rejected and Ha is accepted. In connection with the results of this research, the author provides input for PAK teachers to increase the use of Ice Breaking with students so that student activity increases.